Case Report: Endoscopic radiofrequency ablation with radial-EBUS and ROSE - Zarogoulidis, Paul; Hohenforst-Schmidt, Wolfgang; Papadopoulos, Vasileios; Perdikouri, Eleni-Isidora; Courcoutsakis, Nikolaos; Porpodis, Konstantinos; Matthaios, Dimitrios; Trigonakis, Kostas (Frontiers in Medical Technology, 2023)
Background Single pulmonary nodules are a common issue in everyday clinical practice. Currently, there are navigation systems with radial-endobronchial ultrasound and electromagnetic navigation for obtaining biopsies. Moreover, rapid on-site evaluation can be used for a quick assessment. These small lesions, even when they do not have any clinically significant information with positron emission tomography, are important to investigate. Case description Radiofrequency and microwave ablation have been evaluated as local treatment techniques. These techniques can be used as therapy for a patient population that cannot be operated on. Currently, one verified operating system is used for endoscopic radiofrequency ablation through the working channel of a bronchoscope. Conclusion In our case, a new system was used to perform radiofrequency ablation with long-term follow-up.